Capital Flows to BRICS Countries during 2000-2010 - Munhoz, Vanessa da Costa Val; Deus, Larissa Naves de; Pereira, Vanessa de Paula (Brazilian Keynesian Review, 2017)
The objective of this paper is to analyze the dynamics of financial flows towards the BRICS in the period 2000-2010. Particularly, the paper examines the impacts of the capital controls adopted by each economy on the movements of specific types of capital registered in their financial accounts. The idea is to show that, regarding financial dynamics, the economies of the BRICS present peculiar characteristics that should be taken into account in the formulation of strategies for global financial regulation. To accomplish this goal, Minsky’s theoretical framework is used as background; the cycles of international liquidity are discussed as well as their impact on the behavior of capital flows toward emerging economies, specially the BRICS. The empirical analysis allows us to highlight the importance of an adequate capital management to attract long-term financial flows that are able to contribute to the productive growth of these economies.